The Effectiveness of Village Funds in Bridge Infrastructure Development: A Case Study in Sugihwaras Village - Firdha Irzatullaila; Dwiki Adi Putra; Doris Febriyanti (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This research is titled "Effectiveness of Village Fund Distribution for Infrastructure Development in Sugih Waras Village, Muara Sugihan District, Banyuasin Regency." The study aims to evaluate the extent to which village fund distribution contributes to infrastructure development and community welfare. The methodology employed is a qualitative approach, with data collection through interviews, observations, and documentation. The findings indicate that village funds have been effectively utilized for infrastructure development, such as bridges and health posts, which are relevant to community needs. Community involvement in village deliberations demonstrates a commitment to transparency and accountability. However, challenges related to infrastructure maintenance and the balance between development and community empowerment require further attention. This study recommends enhancing communication and collaboration between the village government and the community to achieve sustainable development.